PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF TEACHING OCCUPATIONAL HYGIENE TO PREVENTIVE MEDICINE STUDENTS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article provides a scientifically grounded analysis of the pedagogical and psychological aspects involved in teaching occupational hygiene to undergraduate students specializing in preventive medicine.
Keywords: Occupational hygiene, pedagogical approach, psychological characteristics, professional motivation, reflective thinking, hygienic thinking, sanitary risk, interactive learning, modeling, medical education.